The 'Million Dollar Inmate': The Financial and Social Burden of Nonviolent Offenders - Ahn-Redding, Heather (Lexington Books, 2007)
What kinds of beliefs do most Americans hold about crime and violence, and where do these beliefs come from? What kinds of people are sent to prison_are the average inmates dangerous criminals, or are they involved in low-level drug-related, property, or public-order offenses? Who is ultimately paying for their time in prison? The 'Million Dollar Inmate' highlights the financial and social costs of America's incarceration of non-violent offenders. With its focus on the specific population of non-violent offenders, this book provides a unique, sociological approach to the problem of handling such a large population at such tremendous costs_paid, for the most part, by taxpayers. Basing her insight on extensive research into the origins of America's correctional systems, the visible and non-visible costs incurred by the practice of incarcerating non-violent offenders, and the goals of the prison system, Heather Ahn-Redding dares to expose flaws in current correctional practices and suggest ways they can be not only changed but also re-envisioned. Ideally suited to researchers, advanced undergraduate students, graduate students, and policymakers.